AIIMS Follow up on Medical Ethics; RTI Act Provided Rescue (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
The Medical Council of India makes it necessary to write the name and registration number of the medical practitioner on all the documents they issue. The doctors’ at the most prestigious institute of the country, AIIMS, New Delhi has forgotten these ethical guidelines and the premier institute is not bothered to make a check to implement these guidelines. The current study takes advantage of the RTI Act, 2005 to learn about the attitude of management towards the implementation of medical ethics and trying to make a change in the policies for the betterment of the medical fraternity and the country at large.
Keywords: AIIMS; Medical Ethics; Registration number; Right to Information Act